Quality of life of healthcare students using active teaching-learning methodology (Research, Society and Development, 2021)
Objective: To evaluate the quality of life of health science students who use active teaching-learning methodology. Methodology: Observational cross-sectional study, carried out at a Public University located in the south-central region of the state of Sergipe. The sample was non-probabilistic for convenience, consisting of 141 students from the courses of nursing, pharmacy, physiotherapy, speech therapy, medicine, nutrition, dentistry and occupational therapy. A characterization instrument and the World Health Organization’s Quality of Life-Bref were applied. Data collection was performed using an online form sent to all students' e-mail. The data were stored and analyzed using BioEstat version 5.0 and GraphPad Prism version 7.0 Results: Health science students had scores below the average of general quality of life and of the physical, psychological, social relations and environment domains in the first, third and fifth cycle of graduation. It was shown that the longer the self-directed study time, the greater the change in quality of life, especially in the psychological domain. Conclusion: The use of active methodologies alters the quality of life of health science students in varied scores and depending on the undergraduate cycle.